“Alguns desenhos guardados aí...” Censorship of Graphic Humor during the Brazilian Military Regime. A case study (Tempo e Argumento, 2022)
This article proposes a reflection on the hybrid and complex motivations of the censorship imposed on the independent press and graphic humor under the Brazilian military regime, based on the analysis of unpublished visual sources. The documents studied are a set of drawings made by cartoonist Nani (Ernani Diniz Lucas) while working in the editorial staff of the satirical weekly Pasquim in the 1970s. Sent to Brasília to be screened by the preventive censorship, the productions were lost for years before being returned to the artist, marked with crosses and other traces of the prohibitions. The drawings thus allow us to enter the world of the censors, making the categories and the very definition of the political more complex: they attest to an overall concern on the part of the authorities for all themes that could undermine the image of a harmonious and modern society, and thus counter the regime's political vision and its authoritarian imaginary.
Keywords: cartoon; censorship; Nani; brazilian military dictatorship